ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN (KASUS: PT. ASTRA AGRO LESTARI, TBK. PT. SALIM IVOMAS PRATAMA, TBK. PT. AUSTINDO NUSANTARA JAYA, TBK. PT. SINAR MAS AGRO RESOURCES AND TECHNOLOGY, TBK. SERTA PT. SAWIT SUMBERMAS SARANA, TBK.) - Febri Yanti Debora Malau; Soulthan Sadin Batubara; Mika Debora Barus (Ensiklopedia Education Review, 2021)
This research was designed to describe the results of financial ratio analysis of palm oil plantation companies listed on the Indonesia Stock Exchange, using liquidity ratios, solvency, activity and profitability. The population in this study are companies listed on the Indonesia Stock Exchange (IDX) is PT. Astra Agro Lestari, Tbk., PT. Salim Ivomas Pratama, Tbk., PT. Austindo Nusantara Jaya, Tbk., PT. Sinar Mas Agro Resources and Technology, Tbk. and PT. Sawit Sumbermas Sarana, Tbk period 2018-2020. This study uses a descriptive method with a saturated sample. The results of this study showed that the liquidity ratio of 3 companies PT. Astra Agro Lestari, Tbk. (AALI), PT. Austindo Nusantara Jaya, Tbk. (ANJT) and PT. Sawit Sumbermas Sarana, Tbk (SSMS) is quite good. . When we view from the solvency ratio of PT. Sawit Sumbermas Sarana, Tbk (SSMS), is the lowest risk of corporate debt and considered the best. When viewed from the activity ratio with total asset turnover of PT Sinar Mas Agro Resources and Technology Tbk.(SMAR) better than other companies, which means it can manage its assets effectively in generating sales. When viewed from the profitability ratio PT Sinar Mas Agro Resources and Technology Tbk.(SMAR) can get much bigger profits than  other companies. With all these ratios, it can be said that PT Sinar Mas Agro Resources and Technology Tbk. (SMAR) has better financial performance than the other four palm oil companies.Keywords : Financial Performance, Financial Ratio, Financial Statements